'Where might we go if we dare': moving beyond the 'thick, suffocating fog of whiteness' in feminism. (December 2019) - Lewis, Gail; Hemmings, Clare
This article explores the multi-pronged relation between individual and collective haunting and political investments in divergent feminist and queer formations. Taking the form of an interview conversation, it traces the trajectories of a political life in sites ranging from the kitchen and the demonstration to the conference and the writing page, and on the way marking the possibilities and limitations of various political-intellectual traditions linked to social justice and freedom in pursuit of being and becoming otherwise. It foregrounds a refusal to accept the terms set by dominant political framings alongside and through a commitment to intersubjectivity and exploration of creative possibility opened up in spaces of excess.